THE ROLE OF PSYCHOLOGICAL FACTORS IN CONSUMER BEHAVIOR (International Journal of Food and Nutritional Sciences, 2023)
The role of psychological factors in consumer behavior is a critical area of study that reveals the intricate dynamics influencing purchasing decisions. This paper explores various psychological elements—such as motivation, perception, learning, beliefs, attitudes, emotions, and personality—and their impact on consumer behavior. Motivation serves as a primary driver, with consumers seeking to satisfy needs ranging from basic physiological requirements to higher-level aspirations like self-actualization. The theory of Maslow's hierarchy of needs exemplifies how these motivations shape consumer choices. Perception plays a vital role in how consumers interpret marketing messages, influenced by individual experiences and biases. Understanding perception enables marketers to craft compelling narratives that resonate with target audiences. Learning, through processes like classical conditioning and observational learning, further informs consumer behavior by creating associations between products and emotional responses.